Effect of lipid composition on incorporation of trastuzumab-PEG-lipid into nanoliposomes by post-insertion method: physicochemical and cellular characterization. (2nd April 2016) - Golkar, Nasim; Tamaddon, Ali Mohammad; Samani, Soliman Mohammadi
Abstract: Context : Anti-HER2 immunoliposomes are promising nanotechnology based systems for active targeting of breast tumors, which depends on the amount of incorporated antibody. Objective/Aim : In this work, we investigated the possible effect of lipid composition on the incorporation of trastuzumab-PEG-PE micelles into nanoliposomes and on their subsequent specific cellular targeting. Materials and methods : Trastuzumab (anti-HER2 monoclonal antibody) was monothiolated and conjugated to maleimide-PEG-PE micelles. Liposomes of different lipid compositions were prepared by the thin layer hydration. Trastuzumab-PEG-PE micelles were incorporated into the liposomes by the post-insertion method. The percentage of lipid mixing was determined based on fluorescence resonance energy transfer. Cellular binding and uptake of rhodamine-labeled immunoliposomes were studied in SKBR-3 (HER2 +++ ) and MCF-7 (HER2 + ) cells. Also, antitumor cell activity of the immunoliposomes was compared to free trastuzumab and the liposomes. Results : The lipid mixing of trastuzumab-PEG-PE micelles depended on the liposome composition. The immunoliposomes containing DPPC, cholesterol and PEG-PE showed prominent lipid mixing. The lipid mixing was consistent with the cell binding results which showed an efficient and specific binding of the immunoliposomes to SKBR-3 cells. Antitumor cell activity of the immunoliposomes in SKBR-3, unlike MCF-7 cells, depended on the content of trastuzumab. Discussion : Cholesterol and PEG-PE in the liposome composition are prerequisites for a successful lipid mixing due to their ability to facilitate fusion. The higher lipid mixing results in higher antibody incorporation and consequently higher targeted cell binding. Conclusions : The lipid mixing depends on the liposome composition, which reflects targeted cell binding of the immunoliposomes.